EFFECTIVENESS OF THE USE OF MAP MEDIA AGAINST SPATIAL LITERACY OF CLASS V ELEMENTARY SCHOOL STUDENTS IN SOCIAL STUDIES (IPS) LEARNING - Dicky Prastya; Winda Maharani (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2018)
This research is motivated by the lack of utilization of the media in conducting learning related to space, making spatial literacy of students less explored. In addition, students tend to be more passive and bored quickly when the teacher in delivering learning comes only from the student's textbook. The lack of understanding of students' spatial literacy, in the end causes students to be less careful in making decisions and also solving spatial problems that occur in everyday life. This research was conducted related to the effectiveness of media maps in social studies learning in class V students of elementary schools in Metro City. The purpose of this study was to provide an understanding of students' spatial literacy, especially in material related to space in social studies subjects. The type of this study is quasi-experimental research using the design of nonequivalent groups pre test-post test from Fraenkel and Wallen. The design of nonequivalent groups pre test - post test was started by setting the experimental group and the control group, then doing the pre test, followed by giving treatment to the two classes and ending with a post test. The subjects in this study were fifth grade elementary school students in Metro City. Data collection techniques in the form of tests. The research instrument is a spatial literacy test sheet. Data were analyzed using normality test and Mann Whitney test. The results of this study indicate that the effectiveness of using media maps in social studies learning can provide an understanding of spatial literacy of fifth grade elementary school students in Metro City. This can be seen from the increase in the correct number of each indicator of spatial literacy that is given in the form of determining the location, identifying spatial orientation, determining the closest distance and identifying objects through symbols on the map. The results of this study can be a suggestion for teachers and schools to continue to facilitate social studies learning with appropriate media, especially media maps for material related to space, so as to provide students with more understanding of spatial literacy. Keywords: media map, spatial literacy, elementary students